INDIRECT SPEECH ACTS OF QUESTIONING IN GONE GIRL MOVIE SCRIPT: A STUDY OF PRAGMATICS - Widyaningsih, Winda (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2018)
The research entitled â€œIndirect Speech Acts of Questioning in Gone Girl Movie Script: A Study of Pragmaticsâ€ analyses kinds of speech acts that is used to convey question. However, this research only focuses on indirect speech acts that speaker used to convey their question. In the research, the writer uses the theory of Speech acts and speech event in Pragmatics and The Study of Language written by George Yule (1996, 2010). Yule reveals that based on the relationship between grammatical structure and the communicative function, sentence can be direct and indirect. Moreover, it also influences by context where the conversation takes place. The research uses descriptive method. The writer collected the data found in Gone Girl movie script and then analyzed the sentences that has a function to make question. After doing the analyses, it can be concluded that to convey their questions, people do not only use interrogative sentence, but also declarative sentence. This is called as indirect speech acts. Indirect speech acts happens when there is an indirect relationship between grammatical structure and its communicative function.